The use of anticoagulants for prevention and treatment of osteonecrosis of the femoral head: A systematic review. Issue 16 (April 2017) - Guo, Peipei; Gao, Fuqiang; Wang, Yanhua; Zhang, Zhenkun; Sun, Wei; Jiang, Baoguo; Wang, Bailiang; Li, Zirong
Abstract: Background: Osteonecrosis of the femoral head (ONFH) is a progressive disease, which mainly affects young adults and often necessitates total hip arthroplasty (THA), so early interventions are critical to successfully protect hip joint from THA. In this review, our purpose was to determine the effects of anticoagulants for preventing and treating the primary and secondary ONFH, respectively, before the collapse stage or before the pathology of necrosis. Methods: We searched PubMed, Embase, Web of Science databases for relevant studies. Any observational or experimental studies that evaluated anticoagulants and ONFH were our goal of searching the electric databases. Results: Four studies including a total of 218 hips were identified in this review, 2 of them were prospective studies which performed by 1 group, 1 was a retrospective study, and the last was a prospective comparative study. Conclusions: Our findings supported that the anticoagulants could be used for primary ONFH. However, anticoagulants cannot play a protective role on secondary ONFH. Moreover, there were no serious adverse effects reported in the studies after anticoagulants treatment. Nevertheless, our present study with some limitations such as the limited sample size only provided limited quality of evidence; confirmation from further systematic review or meta-analysis with large-scale, well-designed randomized control trials is required.